1984
DOI: 10.1017/s0001924000020868
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic large-deflection similitude for oscillating delta wings

Abstract: A similitude has been obtained for delta wings with attached leading edge shock at large incidence in hypersonic flow. A strip theory in which flow at a spanwise location is two-dimensional has been developed. This combines with the similitude to lead to a piston theory which gives closed form solutions for unsteady derivatives in pitch and roll. The derivatives in pitch are independent of and the roll damping derivative varies linearly with the aspect ratio. Substantially the same results as the theory of Liu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The expression for pressure ratio at the nose of the cone in the case of bow-attached shock obtained by Ghosh [11] is given in Eq. (1).…”
Section: Fig 1 Geometry Of Conementioning
confidence: 99%
See 3 more Smart Citations
“…The expression for pressure ratio at the nose of the cone in the case of bow-attached shock obtained by Ghosh [11] is given in Eq. (1).…”
Section: Fig 1 Geometry Of Conementioning
confidence: 99%
“…In the case of an oscillating cone, Ghosh [11] is adopted the equilibrium surface of the cone is perpendicular to the similitude slab at a distance x 1 from the apex. The boat tail helmets can reduce drag studied by Pathan et al, [21] and found that the aerodynamic drag reduces when the helmet shape is streamlined.…”
Section: Fig 1 Geometry Of Conementioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between Lighthill [1] & Mile's, and Ghosh & Mistry's [5] piston theory for the order of two If the shock wave is attached, the angle between the plane and the shock generally relates to the windward surface [3][4]. Ghosh & Mistry [5] has discovered a similitude in hypersonic flow for delta wings with an associated leading edge shock at significant incidence [6]. Hui [3] studied, generated the exact solution in an oscillating wedge for a 2D flow, and obtained the solutions for all supersonic Mach numbers and angle of attack while taking into account the linked shock wave for an oscillating flat plate.…”
Section: Introductionmentioning
confidence: 99%